The effect of family socio-economic status and parents' involvement toward students' mathematics achievement - Yong, Mui Jun. (Universiti Malaysia Sarawak, UNIMAS, 2009)
This study aims to investigate the effect of parents’ involvement and family socio - economic status towards students’ ma thematics achievement. The objective of the study is to investigate the difference in mathematics achievement among students from different level of family socio - economic status and to investigate the relationship between parents’ involvement and student’s mathematics achievement. 180 of Form Four students at SMK Batu Kawa were participated in this study. The data was collected through questionnaire. The finding of the study shows that family socio - economic status contributes effect toward students’ mathema tics achievement . Besides, parents’ involvement was found have positive relationship with students’ mathematics achievement. This study may imply that parents, teacher and school need to be aware with the factors of family socio - economic status and parents ’ involvement in order to improve students’ achievement in mathematics.